Utopía vs. mercado en la construcción de la ciudad finisecular: localismos, sostenibilidad y otros paradignas "post" = Utopia vs. market in the construction of the end of the city: localisms, sustainability, and other "post" paradigms (Polígonos. Revista de Geografía, 2000)
Al igual que un siglo antes, también al finalizar el siglo XX la ciudad es la suma de un sinfín de problemas y contradicciones. La solución a los mismos ha perdido el carácter idealista y utópico que tuvo en el pasado, para entregarse a alternativas socialmente excluyentes, apoyadas en los nuevos paradigmas, políticamente correctos, con los que se quiere justificar la política urbanística y terminar todo un siglo de explotación urbana. Ante esta situación es preciso buscar respuestas consecuentes, es decir, duraderas y universales, a fenómenos que sí lo son y que sólo pueden valorarse adoptando una posición radical ante los mecanismos generadores de la explotación: un planeamiento tecnocrático y cómplice, ante unos instrumentos de gobierno y control social que nunca han abordado las raíces de la desigualdad y en particular los fundamentos de la propiedad del suelo y ante el maquillaje de la sostenibilidad, del urbanismo y de la arquitectura finiseculares.At the end of the 20th century a city is the result of a number of problems and contradictions very similar to what happened a century ago. But the solution to these problems has nothing to do with idealistic and utopian proposals very characteristic of past times. Nowadays the solution has to do with exclusive options that are based on new paradigms, which are correct from a political point of view, and by means of them, it wants to justify the town-planning policy and to put an end to a century of urban exploitation. In view of this position, it is essential to look for consistent lasting and universal answers to a permanent phenomenon and these answers may be valued if we take up a radical position before the generating mechanisms of exploitation. This way, we can devise a form of technocratic planning with regard to some instruments of government and social control, which have never faced up to the origins of social inequality and particularly to the basis of the ownership of the housing estate land. Finally, we must take into account that urban development and architecture are used as an excuse for hiding the urban reality at the end of this century.